Konstruksi Pengelolaan Keuangan Desa Digital Perspektif Tradisi Minangkabau Raso Jo Pareso - Puja Rizqy Ramadhan; Suwarno Suwarno; Shella Pratiwi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to reconstruct the discourse of digital-based village financial management based on the concept of raso jo pareso. This study uses primary data obtained from observations and interviews with informants. The research approach used is a qualitative method. The research paradigm consists of data collection procedures, data presentation, data reduction and drawing conclusions/verification. Based on the results of the study, it can be concluded that there has been a shift in cultural values ​​​​manifested in village financial management. The moral degradation that occurs and regulatory pressures that limit the scope of the actors involved in village financial management. Therefore, it is necessary to revitalize the values ​​​​of raso jo pareso in village financial management which are manifested as shared moral values ​​​​based on fear of God and shame and politeness towards fellow human beings. Thus, a village financial management order is created that upholds moral aspects to have an impact on improving the performance of village entities.